Virus-associated haemophagocytic lymphohistiocytosis in a young Filipino man - Yu, Marc Gregory (BMJ Case Rep, 2016)
Haemophagocytic lymphohistiocytosis (HLH) is a rare syndrome of pathological immune activation characterised by extreme inflammation. We present a case of a young Filipino man consulting for non-specific symptoms of fever, body malaise and weight loss. Prominent physical examination findings included gross pallor, cachexia and hepatosplenomegaly. Laboratory results revealed pancytopaenia, while bone marrow examination revealed haemophagocytosis. Further workup for HLH showed hypertriglyceridaemia, hypofibrinogenaemia and hyperferritinaemia (fulfilling 6 of 8 diagnostic criteria). Exhaustive serological and haematological examinations showed chronic hepatitis B virus infection and past evidence of Epstein-Barr virus infection as possible triggers. The patient was started on antiviral therapy, high-dose steroids and chemotherapy. He initially improved, but eventually succumbed to severe fungal sepsis and pulmonary haemorrhage. An autopsy confirmed the diagnosis of HLH.